PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA DI SMK N 1 DAN SMA N 1 PAINAN KABUPATEN PESISIR SELATAN - Almasri, Almasri; Hanesman, Hanesman (Jurnal Teknik Komputer dan Informatika, 2021)
In an effort to improve the quality of learning in Elementary School, it requires various breakthroughs, both in curriculum development, learning innovation, learning media and the fulfillment of educational facilities and infrastructure. To improve students' learning achievement, teachers are required to make learning more innovative that encourages students to learn optimally both in self-study and in classroom learning. In order for more optimal learning then it is necessary also the learning media should be effective and selective in accordance with the subject taught in improving student achievement. Currently, the implementation of learning process in SMK N 1 and SMA N 1 Painan using thematic pattern with process skill approach and the use of learning media is still not optimal. Few teachers are willing to develop process skills in learning. Similarly, there are still teachers who are less creative in using learning media with various reasons, such as the availability of tools and materials practicum, limited funds, time and others. From the evaluation results obtained the results and benefits of community service activities include improving the skills of teachers SMK N 1 and SMA N 1 Painan Pesisir Selatan in the making of multimedia-based learning media. This devotion activity went smoothly, as various supporters especially participant participation were quite enthusiastic and actively participated in this workshop activity. The workshop activities should be conducted on broader objectives and the material can be developed in the making of learning videos. Thus it is expected later can help Classroom teachers in developing multimedia-based learning media so that the quality of learning SMK N 1 and SMA N 1 Painan South Coastal District can be more increased.